2016
DOI: 10.1063/1.4971441
|View full text |Cite
|
Sign up to set email alerts
|

Optical emission spectroscopy of deuterium and helium plasma jets emitted from plasma focus discharges at the PF-1000U facility

Abstract: Optical emission spectroscopy techniques were used to investigate the spectra of dense deuterium-plasma jets generated by high-current pulse discharges within the large PF-1000U facility and to estimate parameters of plasma inside the jets and their surroundings. Time-resolved optical spectra were recorded by means of a Mechelle®900 spectrometer. From an analysis of the deuterium line broadening, it was estimated that the electron concentration at a distance 57 cm from the electrode outlets amounted to (0.4–3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…It should be noted that in comparison with the optical spectra observed in the previous PF-1000 experiments [2][3][4] the spectra recorded recently in the DPF-1000U facility without the gas-puffi ng showed negligible differences in lines shapes and intensities. Some examples of the optical spectra recorded at different instants before and after the discharge current peculiarity (the so-called current dip) are shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It should be noted that in comparison with the optical spectra observed in the previous PF-1000 experiments [2][3][4] the spectra recorded recently in the DPF-1000U facility without the gas-puffi ng showed negligible differences in lines shapes and intensities. Some examples of the optical spectra recorded at different instants before and after the discharge current peculiarity (the so-called current dip) are shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…The optical emission spectroscopy (OES) has already been used for the investigation of intense pulsed plasma-ion streams generated with the use of the 1 MJ plasma focus facility [1][2][3][4], but recent modifi cations of this machine, and particularly the installation of the gas-puffi ng, have made it necessary to perform anew the detailed spectroscopic measurements. In this note the most important results are presented of experimental studies performed with the use of the modifi ed DPF-1000U facility without and with the gas-puffi ng.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the huge difference in the parameters of astrophysical and laboratory plasma outflows (their sizes differ by 14-15 orders of magnitude, and characteristic densities and pressures by 15-16 orders of magnitude), they can be studied in the framework of the same system of equations (Ryutov & Remington 2002;Remington et al 2006). The first experiments showed that the conditions satisfying the basic laws of similarity, which make it possible to model the jets of young stars, are fulfilled in the PF-1000 (Skladnik-Sadowska et al 2016). It was also shown that in some modes of filling the chamber with working gas, compact plasma objects are formed, which retain their compactness when being spread over considerable distances (Krauz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Результаты последних экспериментов [9][10][11][12][13][14][15] показали, что они также являются эффективным инструментом для лабораторного моделирования одного из вариантов астрофизических джетов -струйных выбросов молодых звёздных объектов (YSO). В экспериментах на установках ПФ-3 [9-12, 14, 15], PF-1000 (Институт физики плазмы и лазерного микросинтеза, Варшава, Польша) [13,14] и КПФ-4 (ГНПО «СФТИ», Сухум, Абхазия) [14,15] продемонстрировано, что компактные плазменные образования могут распространяться на значительные расстояния от места генерации (~1 м), значительно превышающие их поперечные размеры. Для определения природы струйного выброса существенное значение имеет соотношение между плотностью потока энергии электромагнитного поля и плотностью кинетической энергии частиц.…”
Section: Introductionunclassified